A [4Fe-4S] cluster resides at the active center of phosphomevalonate dehydratase, a key enzyme in the archaeal modified mevalonate pathway - Komeyama, Mutsumi; Kanno, Kohsuke; Mino, Hiroyuki; Yasuno, Yoko; Shinada, Tetsuro; Ito, Tomokazu; Hemmi, Hisashi (Frontiers in Microbiology, 2023)
The recent discovery of the archaeal modified mevalonate pathway revealed that the fundamental units for isoprenoid biosynthesis (isopentenyl diphosphate and dimethylallyl diphosphate) are biosynthesized via a specific intermediate, trans-anhydromevalonate phosphate. In this biosynthetic pathway, which is unique to archaea, the formation of trans-anhydromevalonate phosphate from (R)-mevalonate 5-phosphate is catalyzed by a key enzyme, phosphomevalonate dehydratase. This archaea-specific enzyme belongs to the aconitase X family within the aconitase superfamily, along with bacterial homologs involved in hydroxyproline metabolism. Although an iron–sulfur cluster is thought to exist in phosphomevalonate dehydratase and is believed to be responsible for the catalytic mechanism of the enzyme, the structure and role of this cluster have not been well characterized. Here, we reconstructed the iron–sulfur cluster of phosphomevalonate dehydratase from the hyperthermophilic archaeon Aeropyrum pernix to perform biochemical characterization and kinetic analysis of the enzyme. Electron paramagnetic resonance, iron quantification, and mutagenic studies of the enzyme demonstrated that three conserved cysteine residues coordinate a [4Fe-4S] cluster—as is typical in aconitase superfamily hydratases/dehydratases, in contrast to bacterial aconitase X-family enzymes, which have been reported to harbor a [2Fe-2S] cluster.